Residuos Inertes para la Preparación de Ladrillos con Material Reciclable: Una Práctica para Protección del Ambiente - Serrano Guzmán, María Fernanda (2017)
Industrial development and population growth are causing the overproduction of waste. Sometimes these materials, even though are considered inert, are disposed on the land causing alterations to the environment, particularly in the landscape. Examples of these wastes are tires, construction rubbishes coming from pipe and soil, some pruning material and plastic bags. This paper focuses in the use of this kind of waste to prepare masonries of concrete and others with soil; were used both masonries, named ecobricks, to build short walls that were tested in compression strength. The results indicate that the lightweight concrete specimens obtained shown a higher compressive strength than specimens prepared with soil. This research emphasizes the relevance of reuse some material to protect the environment and offering alternatives for reducing the negative impact generated by inadequate disposal.